Aplicações sucessivas de lodo de esgoto no girassol e efeito residual no trigo e triticale - Lobo, Thomaz F.; Grassi Filho, Hélio [UNESP]; Kummer, Ana C. B. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2014)
The objective of this study was to evaluate the effect of factors of production within two years of application of sewage sludge on sunflower and its residual effect on productivity of wheat and triticale. The study was conducted for two consecutive years with sunflower cultivation and after harvest of the second year wheat and triticale were sown without the application of sewage sludge fertilization. The experimental design of randomize blocks was adopted consisting of six treatments and five repetitions: T0 - without nitrogen fertilization; T1 - chemical nitrogen in accordance with Technical Buletin 100. (100% N chemical fertilizers), T2 - 50% Nitrogen from sewage sludge and 50% in the form of chemical fertilizer, top dressing, T3 - 100% of nitrogen recommended for the crop, from sewage sludge, T4 - 150% of nitrogen from sewage sludge; T5 - 200% of nitrogen from sewage sludge. In the sunflower the sewage sludge promoted a higher grain yield and yield of oil accumulated in the two years of application and did not affect the oil content. In triticale the combination of residual effect of two years with sludge and mineral N fertilization resulted in a greater number of plants and a higher yield. In wheat the best treatment was 150% of the dose of N from sewage sludge residual effect of two applications in sunflower.

Neste trabalho se propôs avaliar o efeito da aplicação do lodo de esgoto durante dois anos sucessivos, na cultura do girassol e seu efeito residual na produtividade do trigo e triticale. Trabalhou-se durante dois anos consecutivos com a cultura do girassol semeando-se, após a colheita do segundo ano, o trigo e o triticale sem aplicação de lodo de esgoto. Foi adotado o delineamento experimental em blocos casualizados constituído por 6 tratamentos e 5 repetições: T0 - sem adubação com nitrogênio; T1 - adubação química nitrogenada de acordo com a necessidade de cultura; T2 - 50% adubação nitrogenada proveniente do lodo de esgoto e 50% na forma da adubação química, em cobertura; T3 - 100% da adubação nitrogenada do recomendado pela cultura, proveniente do lodo de esgoto; T4 - 150% da adubação nitrogenada proveniente do lodo de esgoto e T5 - 200% da adubação nitrogenada proveniente do lodo de esgoto. No girassol o lodo de esgoto proporcionou maior rendimento de grãos e de óleo no acumulado dos dois anos de aplicação sem, no entanto, interferir no teor de óleo, no triticale não interferiu no rendimento de grãos enquanto no trigo o melhor tratamento foi o de 150% da dose de N proveniente do lodo de esgoto.
Succesive applications of sewage sludge in sunflower and residual effect on wheat and triticale
Keywords: sustentabilidade; produtividade; nitrogênio; sustainability; productivity; nitrogen